Anastasia at this address - Lowry, Lois. (New York : Bantam Doubleday Dell Books for Young Readers, 1992)
Ready for romance, thirteen-year-old Anastasia answers an ad in the personals with an exaggerated description of herself but soon runs into trouble when the unknown man turns up at a friend's wedding.
"A Yearling book.".
Booklist.
Kirkus Review.
School Library Journal.
6.1
3-6
Keywords: Humorous stories; Letter writing -- Fiction; Humorous fiction; Letter writing -- Fiction